FACTORS AFFECTING AUDIT QUALITY: A LITERATURE REVIEW - Muhammad Boy Sandy; Inten Meutia; Anna Yulianita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Purpose - This scientific article aims to review studies related to factors that canaffect audit quality in the accounting literature during 2012 – 2021. ResearchMethodology - This study was conducted through a web search to identifyrelevant studies using the keywords “factor”, “influence”, and “audit quality”,in which a total of 50 scientific articles that conform to international standardwere identified. Findings - Various factors are thought to affect audit quality,reaching 76 factors. However, the researcher believes only 3 main factors havea dominant effect on audit quality, namely audit fees, auditor experience, and theapplication of auditor ethics, where all those 3 have a significant positive effect.The audit fee affects audit quality positively because it shows the auditor'sexpertise. The experience of the editor shows his skills in accounting andauditing activities. At the same time, professional ethics is helpful forprofessional auditors to work and avoid deviant behaviour. ResearchImplications - This review informs the public that to have audit quality results, itis necessary to pay attention to audit fees, auditor experience, and theapplication of ethics by the auditor. Originality/value - This study tries to findthe factors that dominantly influence